PENERAPAN PEMBELAJARAN MATEMATIKA BERBASIS KOMPUTER BERBANTU SOFTWARE E-LEARNING MATEMATIKA SMP VERSI 5.1. UNTUK MENI NGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP - Menoek Tri Mulyani,; Rifqi Hidayat; Desy Lusiyana (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2018)
This research was conducted to improve students 'mathematical creative thinking abilities and self-awareness by using a new mathematical learning model, the use of the Problem Based Learning model was considered suitable to improve students' mathematical creative thinking abilities and self-awareness because at the stage of solving problems students were required to issue ideas new and students are freed to find their own material resources. This research is a quasi-experimental study conducted in odd semester of 2017/2018 academic year, on July 31 - August 31, 2017 at Weru Islamic Junior High School which is located in Weru Lor Village, Weru District, Cirebon Regency, with the subject of research being VIII grade students of odd semester 2017/2018 lessons. There are two classes used in this study, namely class VIII A as an experimental class and VIII B as a control class, in practice the experimental class uses the Problem Based Learning learning model and the control class uses the conventional model. This research resulted in a difference test of N-Gain mathematical creative thinking abilities obtained sig. (2-tailed) value of less than 0.05 then H0 was rejected. So that it can be concluded that there is an increase in difference between the experimental class and the control class, from the tcount of 6.134 it can be said that the increase in mathematical creative thinking abilities that use the Problem Based Learning model is better than those using conventional learning models and the results of the test differences in the value of N-gain awareness self obtained sig. value (2-tailed) less than 0.05 then H0 is rejected. So it can be concluded that there is an increase in difference between the experimental class and the control class, from the tcount of 7.330 it can be said that the increase in self-awareness of students who use Problem Based Learning models is better than those using conventional learning models. Keywords: Mathematical creative thinking, Self-awareness, Problem Based Learning